The Mathematical Constant of Bound Space at Value 8 And -1 Constant - Cameron, Vinoo (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This paper is to validate by perfect mathematics / geometry the rationale behind the papers of this author published by the journal “Math Lab” and Journal of “Advances in Physics (JAP)” as referenced below. This explanatory paper is complimentary to the published papers. The square (2:2) and a rectangle (1:3) of the same value 8 by length, represents the maximal infinite and the least finite value enclosed by the same value 8 , and that the difference by area is a constant whole number -1 in all of mathematics and physics ( 2*2-1*3=1).